Prevalence and Determinants for Hypertension among Rural Women of Reproductive Age in Indonesia - Crosita Octaria, MIH, dr. Yessi; Khomsan, Ali; Tanziha, Ikeu; Sukandar, Dadang (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
This study aimed to investigate the prevalence and determinants of hypertension in rural women of reproductive age. The cross-sectional study was conducted in Cianjur district on August 2019. It involved 193 married rural women aged 20–49 years old. Independent variables investigated were socio-economic characteristics, anthropometry, fat distribution and nutrient intake. The prevalence of hypertension in the study population using the new American Guideline (ACC/AHA) was 58% in contrast to 23.8% using the European (ESC/ESH) cut offs. Socioeconomic characteristics and nutrient intake showed no significant association with hypertension (p>0.05) while, Body Mass Index (BMI) (p>0.012), Visceral Fat (VF) (p>0.013) and Waist Circumference (WC) (p>0.010) were significantly associated with hypertension. Hence, result of binary logistic regression showed waist circumference is the strongest factor to determine hypertension in our study (OR=2.2; 95% CI: 1.20–4.01). Overall, the use of the American guideline increases the sensitivity of hypertension screening. The use of simple anthropometry measurement of WC combined with BMI can be applied for risk screening of hypertension in the primary health care setting including in the integrated community health post to improve preventive measure. Due to several limitations in the current study, future study should consider larger sample size and addresses history of hormonal contraceptive use as well as physical activity